What to expect when you're expecting a hepatopancreatobiliary surgeon: self-reported experiences of HPB surgeons from different training pathways. Issue 9 (September 2015) - Warner, Susanne G.; Alseidi, Adnan A.; Hong, Johnny; Pawlik, Timothy M.; Minter, Rebecca M.
Abstract: Background: Hepatopancreatobiliary (HPB) surgery fellowship training has multiple paths. Prospective trainees and employers must understand the differences between training pathways. This study examines self-reported fellowship experiences and current scope of practice across three pathways. Methods: An online survey was disseminated to 654 surgeons. These included active Americas Hepato-Pancreato-Biliary Association (AHPBA) members and recent graduates of HPB, transplant–HPB and HPB–heavy surgical oncology fellowships. Results: A total of 416 (64%) surgeons responded. Most respondents were male (89%) and most were practising in an academic setting (83%). 290 (70%) respondents underwent formal fellowship training. Although fellowship experiences varied, current practice was largely similar. Minimally invasive surgery (MIS) and ultrasound were the most commonly identified areas of training deficiencies and were, respectively, cited as such by 47% and 34% of HPB-, 49% and 50% of transplant-, and 52% and 25% of surgical oncology-trained respondents. Non-HPB cases performed in current practice included gastrointestinal (GI) and general surgery cases (56% and 49%, respectively) for HPB-trained respondents, transplant and general surgery cases (87% and 21%, respectively) for transplant-trained respondents, and GI surgery and non-HPB surgical oncology cases (70% and 28%, respectively) for surgical oncology-trained respondents. Conclusions: Fellowship training in HPB surgery varies by training pathway. Training in MIS and ultrasound is deficient in each pathway. The ultimate scope of non-transplant HPB practice appears similar across training pathways. Thus, training pathway choice is best guided by the training experience desired and non-HPB components of anticipated practice.